Cytopathology of Follicular Cell Nodules. (January 2017) - Rossi, Esther D.; Bizzarro, Tommaso; Martini, Maurizio; Larocca, Luigi M.; Schmitt, Fernando; Vielh, Philippe
Abstract : The detection of thyroid nodules, consisting of different diseases, represents a common finding in population. Their evaluation and diagnosis are mostly achieved with fine-needle aspiration cytology (FNAC). Even though the majority of thyroid nodules are correctly diagnosed, a total of 25% to 30% of them are classified "indeterminate" comprising lesions with varying risk of malignancy and different types of management. Although the number of thyroid FNACs, including small lesions, is increasing due to the reliance upon sonographic and cytologic interpretations, there are issues concerning cytomorphologic interpretation and interobserver reproducibility. Different classification systems have tried to better define the criteria for inclusion in specific categories and to therefore reduce the rate of indeterminate diagnoses such as atypia of undetermined significance, follicular neoplasms, and suspicious for malignancy. However, the support of ancillary techniques (eg, immunocytochemistry and molecular analysis) are reshaping morphologic diagnoses made on materials obtained from FNAC.